Information Systems for Engineering and Infrastructure Asset Management - Haider, Abrar; SpringerLink (Online service) (Wiesbaden : Gabler Verlag : Imprint: Gabler Verlag, 2013)
Engineering and infrastructure asset management is information intensive and utilises a variety of information systems. In theory, these systems translate asset lifecycle management plans into action and develop learnings and feedback that inform asset management strategy. This book serves as a comprehensive resource for asset managers to align information systems with strategic asset management information needs; provide integration of asset lifecycle processes to enable an integrated asset lifecycle management paradigm; and evaluate, control, and manage information system based asset lifecycle management. It assists asset managers in better planning, execution, control, and management of asset lifecycle.
Asset Management -- Information Systems for Asset Management -- Towards a Conceptual View of Information Systems Based Asset Management Evaluation -- Information Systems Based EAM in Practice.
Keywords: Economics; Management information systems; Economics/Management Science; Business Information Systems